Исследование результатов сегментации изображений методом матриц совпадений - Яковлева, Е. В.; Кускова, И. В. (НТУ "ХПИ", 2006)
Работа посвящена решению проблем сегментации изображений. Для сегментации текстурных изображений предлагается использовать метод матриц совпадений. Рассмотрена возможность использования этого метода при наличии геометрических преобразований, а также для решения задачи распознавания текстурных изображений.

The subject of this research paper is a development of solutions related to the problem of image segmentation. For the segmentation of textural images it is suggested to use coincidence matrix. The paper also contains a study of deploying this method in all cases that involve geometric transformations as well as of using it as a solution for texture image recognition.
Keywords: зрение компьютерное; текстура; преобразования геометрические